2012
DOI: 10.1177/1010539512469246
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Perceived Stigma, Coping Orientations, Self-esteem, and Quality of Life in Patients With Schizophrenia

Abstract: Stigmatization of mental disorders has detrimental consequences for psychiatric patients. This study examined how perceived stigma and coping orientations of secrecy, withdrawal, and education were related to schizophrenic patients' self-esteem and quality of life (QOL). Coping orientations as mediators of perceived stigma on the outcome variables were also investigated. A total of 80 schizophrenic patients in Singapore participated in the study. Results show that perceived stigma predicted self-esteem over an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
29
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
11
29
2
1
Order By: Relevance
“…Studies on stigma and health have reported that with high level of education attainment there is correspondingly low level of stigma (Ow and Lee 2012). Also this study revealed a significant association between education attained and HIV testing and collection of test results.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies on stigma and health have reported that with high level of education attainment there is correspondingly low level of stigma (Ow and Lee 2012). Also this study revealed a significant association between education attained and HIV testing and collection of test results.…”
Section: Discussionsupporting
confidence: 55%
“…Widespread stigma and discrimination has contributed significantly to thwart the national efforts to roll out PMTCT services to the most needy (Shetty, Marangwanda et al 2008;Tudor Car, Van Velthoven et al 2012). Factors observed to mitigate stigma and discrimination included education as persons with better education are less likely to be negatively affected by stigma and discrimination (Ow and Lee 2012) (Veloso, Bastos et al 2010). Overcoming stigma and discrimination is thus an important component of the ongoing strategies to increase PMTCT coverage in order to achieve national coverage goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result corresponded to other similar studies and showed that stigma‐related stressors were associated with diminished SOC (Lundberg et al . ) and impaired HRQoL (Ow & Lee ; Tang & Wu ; Wang et al . ) among people with severe mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Internalized stigma has been linked to a reduced likelihood of resilient factors including self‐esteem (Mashiach‐Eizenberg et al . ; Ow & Lee ), hope (Livingston & Boyd ), empowerment (Sibitz et al . ), and perceived family support (Korkmaz & Küçük ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation